2012
DOI: 10.1007/s11999-011-2081-x
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic Loosening Rates in Distal Femoral Endoprostheses: Does Stem Size Matter?

Abstract: Background Long-term survival of distal femoral endoprosthetic replacements is largely affected by aseptic loosening. It is unclear whether and to what degree surgical technique and component selection influence the risk of loosening. Questions/purposes We (1) established the overall failure and aseptic loosening rates in a tumor population and asked (2) whether stem diameter and specifically the diaphysisto-stem ratio predicts loosening, and (3) whether resection percentage correlates with failure. Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 25 publications
(41 reference statements)
8
67
0
1
Order By: Relevance
“…Aseptic loosening as the primary cause of the long‐term failure of distal femoral tumor prosthesis failure has been confirmed in other studies, with the incidence of loosening of the tibial component of the prosthesis being very low. The current intramedullary fixations for distal femoral tumor prosthesis are divided into two types: cemented fixation and biologic fixation.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Aseptic loosening as the primary cause of the long‐term failure of distal femoral tumor prosthesis failure has been confirmed in other studies, with the incidence of loosening of the tibial component of the prosthesis being very low. The current intramedullary fixations for distal femoral tumor prosthesis are divided into two types: cemented fixation and biologic fixation.…”
Section: Introductionmentioning
confidence: 80%
“…For the cemented fixation, we used the standard technique which has evolved with the first generation of cement in the 1970s to the current third generation, including thorough expansion of medullary cavity, a cement gun to introduce the cement into the cavity, use of a large‐diameter prosthesis stem, and centralization of the prosthesis stem within the medullary cavity to ensure a uniform distribution of bone cement. An ideal bone cement thickness of approximately 2 mm was used, with a thinner layer likely to cause bone cement fracture. After initial fixation, the long‐term stability of the prosthesis depends on maintenance of a cement‐to‐bone interlocking interface, the quality of the fixation, and the strength of the cement itself.…”
Section: Methodsmentioning
confidence: 99%
“…Early aseptic loosening may occur if a prosthesis with a short stem and a long body is used, because of the insufficient interface between bone and cement and between the cement and the stem. 13 Bergin et al 15 reported, in a study of 34 patients, no failures of distal femoral endoprosthetic arthroplasty in those with a resection of < 40% of the length of the bone; 29% of those with resection > 40% of the length of the bone required revision, at a mean of 12.7 years. This indicated that a greater proportional resection increased the risk of aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Segmental resection and endoprosthetic replacement is the most common method of treatment, but for those patients with long segmental involvement from the metaphysis to a large portion of the diaphysis, a prosthesis with a short stem and a long body will leave the prosthesis at risk of early aseptic loosening. 15,16 An autograft treated with liquid nitrogen A 15-year old female patient had an osteosarcoma in the distal femur. a) MRI showed an osteosarcoma in the metadiaphysial region of the distal femur with massive segmental involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation